Development of biochar-based biocatalysts for fermentative bioethanol overproduction via whole-cell immobilization - Kyriakou, Maria (My University, 2024)
Biofuels have received a lot of attention as an important source of renewable energy, with numerous economic impacts but current biofuel production is based on food crops (first generation biofuels) that compete with agricultural lands and biodiverse landscapes. Bioethanol is considered a feasible, sustainable and enduring energy source. In comparison to traditional liquid transportation fuels, the consumption of biofuels results in zero sulfur emissions and significantly reduces the production of particles and hazardous pollutants. Although bioethanol production is considered as one of the most promising alternatives to the use of petroleum-based fuels, bioethanol fermentations are impacted by substrate and product inhibition decreasing process productivity. The proposed technology exploring the development of biochar-based biocatalysts (BBB), successfully enhanced the efficiency of alcoholic fermentations. Olive kernels, vineyard prunings, sewage sludge and seagrass residues were applied as biowaste for biochar production through pyrolysis at two different temperatures (250 °C and 500 °C), while a commercial type of non-biomass derived char also employed for benchmarking purposes. Three major yeasts were immobilised on materials exhibiting the highest surface areas and applied in repeated batch fermentations using Valencia orange peel hydrolyzates as feedstock. The biocatalysts developed using Sacharomyces cerevisiae and Kluyveromyces marxianus immobilised on vineyard prunings-based biochar exhibited exceptional ethanol productivities. However, Pichia kudriavzevii KVMP10 was not efficient following immobilization on biochar. Immobilised biocatalysts using pistachio-nut shells, peanut shells and corks were also employed in bioethanol fermentations and biochar derived from pistachio shells employing S. cerevisiae was employed in fermentations using citrus peel waste hydrolysate, exhibiting 30.8 g L−1 ethanol concentration at the elevated temperature of 41 oC, while free cells achieved significantly lower concentration (13.4 g L−1). The protective role of using biochar as immobilization carrier against multiple stresses encountered by S. cerevisiae was confirmed by assessing transcription from important metabolic routes involved in the molecular mechanisms triggered during inhibitory bioprocess conditions. Immobilised cells exhibited higher bioethanol titre (39 g L−1) and productivity (7.72 g L−1 h−1) at elevated temperatures compared with the suspended culture that yielded 34 g L−1 and 1.99 g L−1 h−1 respectively. mRNA expression levels of HSP104, HSF1 and TPS, confirmed the protective role of BBB against heat stress. Transcription from MSN2/MSN4 indicated the protective role of cell attachment on the biomaterial against stimulation of the heat shock response route and oxidative stress. Additionally, monitoring transcription of HSP12 and HSP104 demonstrated the beneficial use of the proposed technology. Proline accumulation during osmotic stress further supported the elevated bioethanol productivity achieved by the immobilised system. Non-biological char materials were used in the current study as support materials employing S. cerevisiae in bioethanol fermentations improving the bioprocess performance at elevated temperatures and different dilution rates. Bioethanol production and glucose consumption using immobilised cells of S. cerevisiae on unscreened char was monitored in continuous experiments conducted at 37, 39 and 41 °C. The immobilised system demonstrated stable biofuel production at higher dilution rates as opposed to the conventional system where biomass washout occurred in lower dilution rates. Maximum net bioethanol concentration as well as productivity were significantly via the use of extreme temperature conditions, while the immobilised biosystem assisted the buffering capacity protecting cells and improving the performance of the bioprocess under elevated temperatures and increased dilution rates.
Keywords: Biochar; Bioethanol; Immobilised biocatalysts; S. cerevisiae; Char; Stress tolerance